Moderating Effect of Corporate Governance Mechanism on the Relationship between Firm Attributes and Corporate Performance in Emerging Economy - Omaliko, Emeka; Okpala, Ngozi (Journal of Social Sciences and Management Studies, 2023)
The study examined the moderating effect of corporate governance mechanism on the relationship between firm attributes and corporate performance in emerging economy. Firm attributes was proxy using firm assets tangibility (FAT) and firm foreign listing (FFL); corporate performance was measured using Tobin's Q while the moderating variable of corporate governance mechanism was proxy using board size. The ex post facto design was adopted and the data for the study was collected from the annual reports and accounts of the 66 manufacturing companies listed under consumer goods sector, industrial goods sector oil & gas sector, ICT sector, healthcare sector and conglomerate sector of the Nigeria Exchange Group (NGX) as of December 31, 2022 for the period of 2016-2022. Panel Least squares model was used in the data analysis and the results of the study show a significant and positive association between firm assets tangibility, firm foreign listing and performance of listed manufacturing firms in Nigeria at 1% significant level. Corporate governance mechanism was also found to moderate the relationship between the firm assets tangibility, firm foreign listing and corporate performance at 1%-5% level of significance. The study therefore concludes that firm attributes ensure corporate performance. The study recommends that firms should find a way to ensure an optimal use of their tangible assets and also have a foreign stock listing as it ensures corporate performance. In addition, firms should ensure that they have effective corporate governance mechanism in place as it moderates the relationship between firm attributes and corporate performance.